Resíduos de serviços de saúde em hemocentro: gerenciamento e avaliação do desempenho de tratamento de bolsas de sangue por autoclave - Juice Ishie Macedo (2013)
Health Service Waste(HSW) of Blood Banknoted for biosafety issue. This was an descriptive and exploratory wich aimed to perform a diagnosis of WHS management of a blood bank in Paraná (BBPR) and evaluate the effectiveness of decontamination of blood units positive for HIV, HCV and HBV, by autoclave. The research consisted of two parts, the first relating to the diagnosis of WHS management, and the second on the experimental study with analysis of decontamination of blood bags by autoclave. The first part was conducted documentary analysis and in locu observations with characterization and weighing of WHS and a questionnaire to the manager of the BBPR. The stage 2 ocurred in four stages: Stage 1, in which he conducted pilot testing for adjustments and certification of the autoclave, the 2nd stage was processed in the autoclave 180 blood bags with thermal sensors (ST) out of plastic bags containing blood bags; in the stage 3, was processing 60 blood bags with ST inside (STI) of plastic bags, and, in the stage 4, was analyzing the presence of genetic material in blood bags after autoclaving, the technique of Polymerase Chain Reaction (PCR). The diagnosis of managing HSW revealed 53,7 % of residues in Group D, Group A1 22,76 %, 12,47 % of the Group A4, 10,97 % of Group E, and 0,1 % in Group B; 40 % of HSW, in Group D were recycled and the remaining residue were common. The residues of the Groups A, B and E were transported to treatment outsourced, made by autoclaving or incineration at 450 km from the generation site. Were found inadequacies in the residues segregation in Groups A and D, as well as infrastructure and location incompatible for external storage. As results of the second part of the investigation, the pilot test showed adhesions between the blood bags the need of adapting a stainless basket at the upper end (UE) of the autoclave and reordering of bags. The PCR exam of stage 2nd was positive for single bag contaminated with HBV in the intermediate region (IR) of the autoclave, and the temperature reached 127,6°C with ST out of plastic bags, 6 bags contaminated with HBV distributed in stage 3, the PCR was positive for 2 bags located in the UE, and the maximum temperature reached was 118,4°C with ST inside of plastic bags below the recommended 127°C; analyzes were negative HIV and HCV. The temperature values varied according to the location of the bags and thermal sensors inside the autoclave. Blood bags disruption incidents ranged from 36,7% to 58,5%, while the coagulation indices ranged from 38,3% to 58,3%. It was concluded that BBPR is a major generator of waste, producing 1,36 kg of HSW per bag of blood collected, showing inadequacies in the management of HSW second RDC 306 /2004 evidencing the need for adjustments in the management ofHSW. Regarding the performance of the treatment of blood bags, although the autoclave has been effective for HIV and HCV, it did not eliminate the presence of genetic material of HBV in blood bags contaminated, the conditions in which this research was performed.